Effect of application of hot air humidified as post-harvest technology in the quality of Feijoa - Sanchez-Rubio, David Leopoldo (2020)
The feijoa (Acca sellowiana) is an exotic climacteric fruit in South America, by its attractive sweet and sour flavor; it has been positioned in the market national as international. For this reason, is relevant to advance in the development and application of post-harvest technologies that foster their appropriate management and conservation. This study had as aim to evaluate the effect on postharvest quality of feijoa fruits subjected to a current air at temperature of 41° C and relative humidity of 57% for 2 hours (T1) and for 4 hours (T2). Subsequently, were evaluated physical and chemical parameters during the storage for two weeks in ambient conditions. Was found decrease in the weight loss of treatments in contrast with the control, also the decrease in contraction of the equatorial diameter without detriment of chemical parameters such as pH, titrable total acidity (ATT) and maturity index (IM). Among the two treatments, the best one is T1 (41° C, 57% HR, for two hours) depending on parameters such as the weight loss and contraction of the equatorial diameter, pH, ATT and IM.